Task and task-free FMRI reproducibility comparison for motor network identification - Kristo, Gert; Rutten, Geert-Jan; Raemaekers, Mathijs; de Gelder, Bea; Rombouts, Serge A.R.B.; Ramsey, Nick F. (Human brain mapping, 2014)
Test‐retest reliability of individual functional magnetic resonance imaging (fMRI) results is of importance in clinical practice and longitudinal experiments. While several studies have investigated reliability of task‐induced motor network activation, less is known about the reliability of the task‐free motor network. Here, we investigate the reproducibility of task‐free fMRI, and compare it to motor task activity. Sixteen healthy subjects participated in this study with a test‐retest interval of seven weeks. The task‐free motor network was assessed with a univariate, seed‐voxel‐based correlation analysis. Reproducibility was tested by means of intraclass correlation (ICC) values and ratio of overlap. Higher ICC values and a better overlap were found for task fMRI as compared to task‐free fMRI. Furthermore, ratio of overlap improved for task fMRI at higher thresholds, while it decreased for task‐free fMRI, suggesting a less focal spatial pattern of the motor network during resting state. However, for both techniques the most active voxels were located in the primary motor cortex. This indicates that, just like task fMRI, task‐free fMRI can properly identify critical brain areas for motor task performance. Although both fMRI techniques are able to detect the motor network, resting‐state fMRI is less reliable than task fMRI. Hum Brain Mapp 35:340–352, 2014. © 2012 Wiley Periodicals, Inc.